Hak Waris Karena Nikah Sirri - Jauhari, Jauhari (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Regarding the inheritance rights of a siri marriage, what is the essence of inheritance of a siri marriage according to Islamic law and what is meant by inheritance of a siri marriage according to the decision of the Palembang religious court. This research method is normative juridical in nature. Research is usually carried out by examining statutory regulations and other statutory regulations related to the subject under study, namely the decisions of the religious courts analyzed in this research. Based on the results of the examination, inheritance rights arising from unregistered marriages are subject to the laws and provisions of Islamic law, and the following laws apply in the use of law to decide the case. Lawmakers and sharia ensure that the parties making decisions receive their fair share in accordance with its provisions.